Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pengguna Jasa Tata Rias Pengantin Jawa “Solo Basahan” (Studi Kasus di Kota DKI Jakarta): Penelitian - Mega Kartika; Sri Widjajanti; Dwi Atmanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
When it comes to Javanese wedding makeup services, customer satisfaction is influenced by both the quality of the service and the pricing. There are indicators that the degree of satisfaction that customers have with the services provided by Solo Basahan is not yet at its highest possible level. The purpose of this research is to determine the extent to which the quality of service and the cost affected the level of satisfaction experienced by customers of the "solo basahan" wedding cosmetics service in Javanese. In this research, a quantitative methodology is used, and data collection is accomplished via the use of questionnaires and purposeful sampling. There were a total of 32 service users that participated in the study. According to the findings, the computation of the t-test yields a significant value of 0.001 less than 0.05, which indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This substantiates the presence of a considerable effect on the level of satisfaction experienced by consumers. A value of 0.960 was obtained for the coefficient of determination (R-square), which indicates that 96.2% of service quality and price have a significant impact on other variables. The remaining 3.8% of the influence is attributed to other elements of other variables. It is possible to draw the conclusion that the level of satisfaction experienced by customers is significantly impacted by both the quality of the service and the pricing.